Deglycosylation Increases the Fibrinolytic Activity of a Deletion Mutant of Tissue-Type Plasminogen Activator - Wilhelm, James; Kalyan, Narender K; Lee, Shaw Guang; Hum, Wah-Tung; Rappaport, Ruth; Hung, Paul P (Thrombosis and Haemostasis, 1990)
Δ2−89 t-PA is a deletion mutant lacking the finger (F) and epidermal growth factor (EGF) domains; thus, the fibrin interaction of this molecule must be mediated solely by the kringle region. In the present study, the influence of the oligosaccharide side-chains on the activity of Δ2−89 t-PA has been investigated. Δ2−89 t-PA was secreted in two forms, designated I and II, which presumably differ by the lack of one asparagine-linked oligosaccharide in the kiiugle 2 domain of form TT, Forms I and II of Δ2−89 t-PA weie puiified; form II displayed higher fibrinolytic activity than form I. When foini I was partially deglycosylated or treated to remove sialic acid, fibrinolytic activity was increased. Production of Δ2−89 in the presence of timicamycin led to secielion of a glyean-free activator with higher activity. These findings suggest that certain oligusacchaiide side chains, particularly (hose containing sialic acid, can interfere with the interaction between the kringle region of t-PA and fibrin.